PEMANFAATAN TANAMAN ECENG GONDOK (EICHORNIA CRASSIPES) UNTUK KERAJINAN TAS - Abdurrozzaq Hasibuan; Ade Putri Pertiwi Hasani; Nurhabibah Nasution; Shofiah Muhabbah Hasibuan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Watelr hyacinth (Elichomia crassipels) is a floating aqulatic plant that delvellops velry fast so it is considelreld damaging to thel aqulatic elnvironmelnt. Thelrel arel selvelral obstaclels that occulr, sulch as thel lack of practical managelmelnt of bags madel from watelr hyacinth starting from thel procelss of pullling, drying, sellelcting, splitting, and welaving. This practicel caulsels thel relsullts to bel too timel-consulming so that it is too latel to melelt markelt delmand Aims to elxplorel thel potelntial ulsel of watelr hyacinth plants in thel produlction of handicraft bags this stuldy aims to elxplorel thel potelntial ultilization of watelr hyacinth plants in thel produlction of handicraft bags thel melthod ulseld incluldels collelcting samplels of watelr hyacinth plants. procelssing plant fibelrs, as welll as making bags ulsing watelr hyacinth plant fibelrs. Thel relsullts showeld that watelr hyacinth plant fibelrs can bel procelsseld into strong and dulrablel matelrials for craft bags. Thel procelssing procelss incluldels washing, drying, blelaching and tying thel fibelrs into yarn or woveln. Watelr hyacinth has an intelrelsting telxtulrel and ulniqulel stylel. In addition, thel ulsel of watelr hyacinth plants for craft bags also has elnvironmelntal belnelfits. This plant can bel considelreld as a relnelwablel and elnvironmelntally frielndly relsoulrcel. belcaulsel it can hellp control thel elxcelssivel growth of watelr hyacinth in thel waters.